Porphyrin biosynthesis. VIII. Avian erythrocyte porphobilinogen deaminase-uroporphyrinogen III cosynthetase, its purification, properties and the separation of its components - Llambías, E.B.C. (1971)
1. 1. A method for the isolation and purification of porphobilinogenase, porphobilinogen deaminase and uroporphyrinogen isomerase from avian erythrocytes is described. 2. 2. Some properties of the isolated enzymes were studied. The optimal pH for porphobilinogenase and deaminase was 7.4. Purified porphobilinogenase was resolved into three bands on starch gel electrophoresis. The molecular weight of the purified enzymes was determined by gel filtration. The presence of porphobilinogen or NH4 + at certain concentrations afforded protection against heat inactivation of isomerase, the heat labile enzyme. Initial porphyrin formation by porphobilinogenase was linear with time. 3. 3. The action of various compounds added to the system was studied. Thiol reagents inhibited both porphobilinogenase and deaminase, indicating the presence of thiol groups essential for activity. NH4 +, hydroxylamine, adenine, ADP, ATP, some dicarboxylic acids and 2-methoxy-5-nitrotropone inhibited deaminase. © 1971.